Factors Influencing The Placement of Subordinates A Analysis of Labor Market Information Service of Cooperations and Manpower Kerinci District - Suhaidir, Suhaidir (Green Publisher, 2023)
Based on the Regulation of the Minister of Manpower of the Republic of Indonesia Number 39 of 2016 concerning Manpower Placement can be done with a manual system and online services, in the placement of workers with these two systems, Human Resource Management greatly influences directly or indirectly . The element of HRM is human, human resource management also involves the design and implementation of planning systems, preparation of needs of subordinates and employee development, career management, performance evaluation, employee competency and good employment relations, factors influencing employee placement based on Market Information Analysis Work at the Office of Cooperatives and Labor in Kerinci Regency. Many companies, labor users are connected to information on the labor market, special job fairs (BKK) and job fairs, to make it easier to place sufficient subordinates and understand the requirements, without having to pay high costs, to get employees, subordinate laborers who meets the standards of competence.